Design and Implementation of Planar Fourtear Microstrip Antenna for WLAN and WiMAX Applications - Ken Paramayudha; Yuyu Wahyu; Aprilia Pustpita Sari; Heroe Wijanto (National Research and Innovation Agency, 2016)
In this paper, the microstrip planar fourtear antenna that operate at frequency range 2300 – 2500 MHz was investigated, Some applications suitable to operate in this frequency are WiMAX at 2.3 and 2.5 GHz and WLAN at 2.4 GHz. Simulations performed with the aid of Finite Element Emthod (FEM) based software which can calculte and comply the appropriate design to be able to operate at the desired working frequency. The analyzed parameters include : SWR, impedance, return loss, radiation patterns, gain, and polarization. From the measurement, bandwidth obtained is equal to 7.69% in the frequency range of 2318,250-2500 MHz in VSWR < 2. Radiation pattern measurement was unidirectional and the polarization was elliptical.